Efek ukuran panjang cangkang terhadap Indeks Kondisi, dan Kandungan Logam Timbel Kerang Hijau (Perna viridis) (Effects of Shell Length on the Condition Index, and Lead Content of Green Mussel (Perna viridis) ) - Khusnul Yaqin (Jurnal Pengelolaan Perairan, 2018)
Condition Index (CI) of mussel is one of parameters used to analysis mussel health.  Interstingly, many researchers produce different CI formula.  This study was conducted to study the most appropriate CI formula to determine the health of green mussel, Perna vidiris. Four hundred of green mussel were colected from pollueted (Makassar) and expected unpolluted (Mandalle, Pangkajene and Kepulauan/Pangkep) areas. Afterward, the mussels were tranfered using cool box to laboratory for further analysis.  Some morphomometry parameters, tissue and shell weigth were measured to fulfil 10 types of CI formula. Lead content of mussel’s tissue was analyzed using AAS (Atomic Absorption Spectrophotometry). The result revealed that the use of CI1-6 and 9 were influenced by shell lenght.  In contrast, the use of CI7 and 8 were not affected by shell length. The average of lead content in mussel’s tissue was 7.87 ± 0.53.  This value has exceeded the consumption threshold for shellfish biota.The results suggested that CI 8 is the most practical condition index used for environmental monitoring. Keywords : Valuable Condition Index, Makassar Waters, Toxicity of Lead, Eco-sentinel Organism, green mussel health